Hardware module development for RFID drone - Arunachalam, Muthukkumar (2018)
Nowadays most of the industry or stores uses RFID (Radio Frequency Identification) technology to monitor the state of the product. But, sometimes there is a difference between registered and the real value. In big stores manual inventory is very hard, expensive and time consuming process. In the present decades many researches are going on to avoid the above problem and one of the solutions is to use drones for RFID inventory. This project is focused on designing and developing hardware for RFID drone to aid RFID inventory and development of a software module capable for reading of tags data. The project presents analysis of the hardware devices such as Passive UHF (Ultra High) RFID Reader, Antenna, CPU (Central Processing Unit), PSU (Power Supply Module) and other interfacing components. Selection of the devices is based on criteria such as size and weight, market options and the components which is going to be used for RFID drone. Finally, software coding to read the RFID tags.